1999
DOI: 10.2337/diacare.22.9.1445
|View full text |Cite
|
Sign up to set email alerts
|

Discordance between physician and adolescent assessments of adherence to treatment: influence of HbA1c level. The PEDIAB Collaborative Group.

Abstract: By identifying the possible discrepancy between their own assessment of adherence and that of adolescents, and by avoiding the systematic attribution of poor metabolic control to poor adherence, physicians could generate a more confident and collaborative relationship with diabetic adolescents and therefore facilitate adolescents' self-management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 0 publications
3
25
1
Order By: Relevance
“…In an earlier study, the rate of discordance on adherence to drugs between patients and physicians was 35% [18] which is significantly lower than what we have reported. Again, the rate of discordance in our study is lower than that previously reported in HIV-infected people where adherence was measured by electronic monitoring 41% [8], self-report 45% [11] or even with a study carried out on adherence to treatment for diabetic adolescents [19]. Despite the fact that the rate of discordance is lower than in some other studies, substantial gap has been found between patients and physicians.…”
Section: Discussioncontrasting
confidence: 95%
“…In an earlier study, the rate of discordance on adherence to drugs between patients and physicians was 35% [18] which is significantly lower than what we have reported. Again, the rate of discordance in our study is lower than that previously reported in HIV-infected people where adherence was measured by electronic monitoring 41% [8], self-report 45% [11] or even with a study carried out on adherence to treatment for diabetic adolescents [19]. Despite the fact that the rate of discordance is lower than in some other studies, substantial gap has been found between patients and physicians.…”
Section: Discussioncontrasting
confidence: 95%
“…The literature describing the diabetes professional-patient relationship suggests that wellintentioned professionals sometimes misjudge the perspective of families, thereby missing opportunities to be of greatest service. [27][28][29][30] This discussion organizes the parents' perspective into several themes, each of which describes an aspect of a multilayered approach that health professionals might use to optimize care for patients with diabetes. Qualitative insight from the preliminary analysis of the focus groups and interviews are included to describe the subtext behind some of the ideas.…”
Section: Discussionmentioning
confidence: 99%
“…With this in mind, it is not surprising that adherence declines during adolescence. 30,41 Hanna and Guthrie 12 found that parental involvement in diabetes management decreased from early to middle to late adolescence. Anderson and colleagues 42,43 reported that children and adolescents whose parents were more involved in diabetes management tested blood sugar more frequently and were in better glycemic control.…”
Section: Supporting Children and Adolescentsmentioning
confidence: 97%
“…Interestingly, Du Pasquier-Fediaevsky and Tubiana-Rufi [33] reported very low agreement between adolescents' and physicians' perception of adherence. Adolescents saw themselves as more adherent.…”
Section: Metabolic Control Behavioral Assessment and Interventionsmentioning
confidence: 97%